The Great Unknown : Japanese American Sketches - Robinson, Greg, 1966- (Book collections on Project MUSE., 2016)
"Introduces a readable collection of portraits about a group of extraordinary men and women who made remarkable contributions in the arts, literature, law, sports, and other fields, and shed light on largely unknown aspects of Japanese American history"--Provided by publisher